Epistemic uncertainty modeling: The-state-of-the-art - Hung T. Nguyen (2018)
© Springer International Publishing Switzerland 2015. This paper is about the state-of-the-art of epistemic uncertainty modeling from subjective probability (Thomas Bayes) to fuzzy measures (Michio Sugeno).